Quantifying morphological and genetic variation of sympatric populations to guide conservation of endangered, micro‐endemic springsnails. Issue 4 (4th December 2013) - Morningstar, Cayla R.; Inoue, Kentaro; Sei, Makiri; Lang, Brian K.; Berg, David J.
ABSTRACT The endangered snails Juturnia kosteri and Pyrgulopsis roswellensis are endemic to springs on Bitter Lake National Wildlife Refuge, NM, USA. These species are small and difficult to distinguish by shell shape. A morphological analysis of these two species was conducted using geometric morphometrics, and a phylogenetic analysis using the mitochondrial DNA genes COI and ND1 was performed. Principal component analysis showed significant overlap in shell shape between the two species. Phylogenetic analysis showed that the two species formed monophyletic clades, with each containing low genetic diversity. Analysis of molecular variance for each species showed significant variation among populations. Both species showed significant isolation‐by‐distance, but only P. roswellensis showed a significant relationship between shell shape and geographic distance. The overlapping ranges and the similarity in shell morphology suggest that these micro‐endemic species are difficult to distinguish in the field, particularly by non‐specialists. This presents challenges to population management of these species. Divergence among populations within each species indicates isolation at very small geographic scales. Because these desert springs are home to endemic species within a variety of invertebrate groups, they are likely to contain significant amounts of yet‐to‐be‐discovered biodiversity; many of these unknown taxa are also likely to be of conservation concern. Copyright © 2013 John Wiley & Sons, Ltd.